Mapping a brain parasite: occurrence and spatial distribution in fish encephalon - Born-Torrijos, Ana; van Beest, Gabrielle S; Merella, Paolo; Garippa, Giovanni; Raga, Juan Antonio; Montero, Francisco E (International journal for parasitology. Parasites and wildlife, 2023)
Parasites, especially brain-encysting trematodes, can have an impact on host behaviour, facilitating the transmission to next host and completion of the life cycle, but insufficient research has been done on whether specific brain regions are targeted. Using Cardiocephaloides longicollis as a laboratory model, the precise distribution of metacercariae in experimentally-infected, wild and farmed fish was mapped. The brain regions targeted by this parasite were explored, also from a histologic perspective, and potential pathogenic effects were evaluated. Experimental infections allowed to reproduce the natural infection intensity of C. longicollis, with four times higher infection intensity at the higher dose (150 vs 50 cercariae). The observed metacercarial distribution, similar among all fish groups, may reflect a trematode species-specific pattern: metacercariae occur with highest density in the optic lobe area (primarily infecting the periventricular gray zone of optic tectum) and the medulla oblongata, whereas other areas such as the olfactory lobes and cerebellar lobes may be occupied when the more frequently invaded parts of the brain were crowded. Mono- and multicysts (i.e. formed either with a single metacercaria, or with 2-25 metacercariae encapsulated together) may be formed depending on the aggregation and timing of metacercariae arrival, with minor host inflammatory response. Larvae of C. longicollis colonizing specific brain areas may have an effect on the functions associated with these areas, which are generally related to sensory and motor functions, but are also related to other host fitness traits such as school maintenance or recognition of predators. The detailed information on the extent and distribution of C. longicollis in fish encephalon sets the ground to understand the effects of brain parasites on fish, but further investigation to establish if C. longicollis, through purely mechanical damage (e.g., occupation, pressure and displacement), has an actual impact on host behaviour remains to be tested under controlled experimental conditions.
Keywords: Histology; Trematoda; Cardiocephaloides longicollis; Microhabitat selection; Brain-encysting